Konstruksi Keamanan Kepabean Dalam Framing Media Sosial Bea Cukai Batam 2025 - Gusri, Latifah; Anisa, Ria (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
The transformation of Batam Customs from an administrative authority into a maritime security actor has become increasingly visible through digital communication practices on social media. In 2025, customs issues in the city of Batam are no longer positioned only as fiscal and administrative matters, but are constructed as multidimensional threats to economic security, society, state sovereignty, and the environment. This shift takes place through framing processes that are continuously and intensively produced and distributed in digital spaces. This Study aims to analyze how the social media framing of Batam Customs shapes the construction of maritime security and functions as a mechanism to legitimize state security actions. The research utilises a qualitative approach with digital ethnography (netnography) within a constructivist paradigm. Data analysis applies Robert N. Entman’s framing model and Barry Buzan’s securitization theory to examine Batam Customs’ Instagram content published between January and December 2025, which is categorized into Education, Work Visits/Surveillance and Enforcement, Protection Service, Achievement, and Transparency. Data collection is conducted through digital observation and documentation of texts, visual materials, and user interactions. The findings show that customs issues are consistently framed as multidimensional threats to economic security, society, state sovereignty, and the environment. Batam Customs is no longer understood as an administrative institution, but as a maritime security actor performing a state protection function. This framing operates as a mechanism of symbolic legitimacy that normalizes surveillance and coercive enforcement actions, while shifting public perception of customs from an administrative matter toward a maritime security regime through repeated, visual, and emotional narratives on social media. In conclusion, social media functions as a space of digital securitization in maritime border security practices, strengthening the symbolic legitimacy of the state through strategic visual representations and narratives rather than through formal policy alone.